Prevalence of coexisting autoimmune thyroidal diseases in coeliac disease is decreasing. Issue 2 (March 2020) - Castro, Patricia Dominguez; Harkin, Grace; Hussey, Mary; Christopher, Brian; Kiat, Clifford; Chin, Jun Liong; Trimble, Valerie; McNamara, Deirdre; MacMathuna, Padraic; Egan, Brian; Ryan, Barbara; Kevans, David; et al.
Background: Coeliac disease (CD) is associated with an increased risk of other immune-mediated conditions. Aim : To investigate the prevalence of coexistent immune-mediated diseases in CD patients, and changes in the prevalence of autoimmune thyroidal diseases over the last 50 years. Methods: Medical record data were collected retrospectively from 749 CD patients in Ireland. Prevalence of autoimmune diseases was compared with previously published results from general populations. Patients were divided into four groups based on the year of diagnosis to analyse changes in the prevalence of autoimmune thyroidal disease over time. Results: Median age at the time of CD diagnosis was 56 years (range 18–91 years). A total of 233 (31.1%) patients had a coexistent immune-mediated condition (IMC). Autoimmune thyroidal diseases were seen in 149 (19.9%) patients, hypothyroidism in 110 (14.7%), type 1 diabetes in 27 (3.6%), psoriasis in 20 (2.7%), inflammatory bowel disease in 14 (1.9%) and rheumatoid arthritis in 12 (1.6%). All conditions were more common in CD patients than in the general population. Type 1 diabetes was diagnosed mainly before CD, whereas there was no such trend in other conditions. Autoimmune thyroidal diseases became less common in female CD patients over time. Conclusions: Prevalence of autoimmune diseases is increased in adult CD patients compared with the general population. However, concomitant autoimmune thyroidal diseases became less common over time in women.